Case-method as the Possibility of Implementing Competence-based Approach in Conducting Classes on Forensics - Svetlana Evgeneevna Tymoshenko (Сибирское юридическое обозрение, 2011)
This paper is devoted to the implementation of competence-based approach in the teaching of criminology. The author examines the possibility of using case-method for practical training. The author concludes that instructors should pay greater attention to practical and laboratory work of students.